(untitled) (Journal of Bangladesh Academy of Sciences, 2009)
Air particulate matter (PM) level and its constituents (black carbon, organic carbon and selected trace metals) were investigated from samples of a field campaign from Tajgaon Industrial area in Dhaka City. The sampling was done from November 2006 to April 2007 using MiniVol Portable AirMetrics samplers. The samples were collected in two fractions of 0-2.5 µm and 0-10 µm sizes using two samplers simultaneously. It has found that both PM10 and PM2.5 values were higher than the 24-h average Bangladesh national ambient air quality standard. From statistical analysis of the PM composition data coupled with reconstructed mass (RCM) technique, five major local sources could be identified those contributing to PM mass. Although PM samples were collected from an industrial area, vehicular emissions constituted the major source of air pollution and possibly some regional emission sources are also responsible for high PM2.5 and BC concentrations in Dhaka, especially during wintertime. It is also observed that PM2.5, PM10 and BC concentration levels at a receptor site largely depend on the meteorological conditions including rainfall, wind speed and wind direction. Key words: PM10, PM2.5, MiniVol sampler DOI: 10.3329/jbas.v33i1.2952 Journal of Bangladesh Academy of Sciences, Vol. 33, No. 1, 71-85, 2009